2016
DOI: 10.1017/s0007114516001537
|View full text |Cite
|
Sign up to set email alerts
|

The combined effects of soya isoflavones and resistant starch on equol production and trabecular bone loss in ovariectomised mice

Abstract: Equol is a metabolite of the soya isoflavone (ISO) daidzein that is produced by intestinal microbiota. Equol has greater oestrogenic activity compared with other ISO, and it prevents bone loss in postmenopausal women. Resistant starch (RS), which has a prebiotic activity and is a dietary fibre, was reported to promote equol production. Conversely, the intestinal microbiota is reported to directly regulate bone health by reducing inflammatory cytokine levels and T-lymphocytes in bone. The present study evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 60 publications
(85 reference statements)
4
28
0
Order By: Relevance
“… 223 , 230 Additionally, equol can inhibit the expression of relevant inflammatory cytokines in bone marrow in a dose-dependent fashion due to estrogen deficiency or LPS from intestinal pathogens. 231–233 Although produced by gut microbiota, equol may modify gut microbiota diversity and composition in turn. 231 Isoflavone metabolism can promote the growth of Clostridium clusters XIVa and IV and suppress the genera Bacteroides and Parabacteroides .…”
Section: Host and Microbiota Interactions In The Pathogenesis And Trementioning
confidence: 99%
See 1 more Smart Citation
“… 223 , 230 Additionally, equol can inhibit the expression of relevant inflammatory cytokines in bone marrow in a dose-dependent fashion due to estrogen deficiency or LPS from intestinal pathogens. 231–233 Although produced by gut microbiota, equol may modify gut microbiota diversity and composition in turn. 231 Isoflavone metabolism can promote the growth of Clostridium clusters XIVa and IV and suppress the genera Bacteroides and Parabacteroides .…”
Section: Host and Microbiota Interactions In The Pathogenesis And Trementioning
confidence: 99%
“… 231–233 Although produced by gut microbiota, equol may modify gut microbiota diversity and composition in turn. 231 Isoflavone metabolism can promote the growth of Clostridium clusters XIVa and IV and suppress the genera Bacteroides and Parabacteroides . 234 Nevertheless, equol production from dietary phytoestrogens has significant interpersonal variations, predominantly depending on gut microbial composition and potential correlations among the three groups of phytoestrogen metabolism as well as dietary components.…”
Section: Host and Microbiota Interactions In The Pathogenesis And Trementioning
confidence: 99%
“…To date, very few studies have evaluated a link between prebiotic-induced microbial changes in the gut with improvements in calcium absorption and/or markers of bone health. Of the animal studies that have explored this interaction, bifidobacteria and Bacteroides have been identified as mediators of calcium absorption, intestinal morphological and pH changes, and improved bone strength [ 26 , 75 77 ]. Two recent studies of adolescent calcium absorption which aimed to correlate improvements in calcium absorption with changes in the gut microbiota found that SCF increased Bacteroides , Butyricicoccus , Oscillibacter , Dialister, Parabacteroides, and Clostridium [ 42 , 43 ].…”
Section: Local Intestinal and Systemic Effects Of Prebioticsmentioning
confidence: 99%
“… 76 ) Resistant starch (RS), soy isoflavones (IF) 4 diets: control, 0.05% IF, 9% RS, and 0.05% IF + 9% RS, for 42 days Parallel design; 5 groups: OVX or sham controls on AIN-93G with corn oil instead of soybean oil; 3 groups consumed supplemented diets; 4 day run-in on AIN-93G; IF/RS replaced sugar/cornstarch in diet; animals pair-fed Female ddY mice ( n = 35), age 8 weeks Femur BMD and trabecular microarchitecture; cecal content weight and pH; amplification of the fecal bacteria 16S DNA and terminal restriction fragment length polymorphism; bone marrow inflammation IF + RS increased equol production, prevented the OVX-induced decline in trabecular BMD of the distal femur and improved inflammation in bone marrow; no difference in bone measures between IF + RS and IF diets; diets with RS increased cecal bifidobacteria content Tousen Y, et al 2016 (Ref. 77 ) Resistant Starch (RS60 and 75), Soluble Corn Fiber (SCF), Soluble Fiber Dextrin (SFD), Pullulan, Polydextrose (PDX), Inulin, and Synergy1 ® (Inulin + FOS) 4% of prebiotic by weight of diet, for 12 weeks Parallel design, SI; initially 2 weeks of diets were AIN-93G + 10% prebiotic but due to loose stools in several groups, the % fiber was reduced to 5% after 2 weeks for all treatments and again after another 3 weeks in SCF, SFD, and PDX groups to 4% prebiotic and 1% cellulose; prebiotics replaced cornstarch in diets Male Sprague Dawley rats ( n = 150), age 4 weeks Ca absorption and mineral (Ca, Zn, Fe, Mg, K and Cu) retention; whole-body BMD, BMC and body composition by DXA; bone density (by water displacement), pQCT and bone-breaking strength of femurs; cecal morphology and fecal SCFA concentrations Whole-body BMD and BMC were greatest following SCF and SFD consumption; Ca and Mg concentrations in bone and femur contents were improved by RS60, RS75, SFD, PDX, inulin and inulin/FOS; Cu retention was improved by all fibers except inulin; Zn femur content was improved by all fibers but pullulan and SCF; Fe retention was improved by SCF; cecal content weight improved with SFD, SCF, PDX, inulin and Synergy1 ® ; all fibers except RS60 and RS75 increased total SCFA and propionate in the cecum; peak breaking force of femurs was significantly improved by SCF and SFD Weaver C, et al 2010 (Ref. 41 ) sc-FOS 0 or 100 g/kg of sc-FOS, for 10 days Parallel design; adequate Ca diet (0.5%) or low Ca diet (0.01%) were administered in conjunction with both sc-FOS treatments Male Sprague Dawley rats ( n = 20), age 4 weeks Serum Ca concentration; calbindin D9k protein expression; circulating markers of vitamin D and Ca metabolism; small intestine and cecum weight sc-FOS increased calbindin D9k expression in the large intestine; changing the ...…”
Section: Evidence From Preclinical Modelsmentioning
confidence: 99%
“…All the rats were fed an AIN‐93G‐based diet (Tousen et al ) (composition in g/kg): corn starch 529.486 g, casein 200 g, sucrose 100 g, canola oil 70 g, cellulose powder 50 g, mineral mix (AIN‐93G) 35 g, vitamin mix (AIN‐93) 10 g, l ‐cystine 3 g, choline bitartrate 2.5 g, tert‐Butyl hydroquinone 0.014 g. They were allowed free access to food and water, except for 7 h while rats in the Ex‐6h group were exercising. Food intake and body weight were recorded every other day.…”
Section: Methodsmentioning
confidence: 99%